Przygotowanie dzieci w wieku przedszkolnym do pełnienia ról zawodowych = Preparing pre-school children to perform professional roles - Lis-Zaldivar, Anna (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
Man is active throughout his adult life. He is preparing for this role for several years, and already in the process of working on the acquired foundation he refines his skills and competences and gaining new ones. In the concept of "lifelong learning", permanent development is included. At the age of kindergarten, he prepares to perform professional roles. This process is multi-faceted.
Keywords: zawód; praca; przedszkole; dziecko; occupation; work; child; kindergarten